A Study on the Impact of Watershed Compensation Policies on Green Technology Innovation Ecosystems - Mo Li; Jianhua Zhu; Hua Dong (Systems)
This study uses the implementation of the watershed compensation policy as a quasi-natural experiment and selects a sample of 53 cities located within the four major watersheds from 2005 to 2022. By employing a staggered difference-in-differences model and a synthetic control difference-in-differences model, the study investigates how watershed compensation policies influence green technology innovation ecosystems and delves into the underlying mechanisms that are responsible for these impacts. The research reveals the following findings: (1) The introduction of the watershed compensation policy markedly boosts the development of green technology innovation ecosystems in the pilot cities, and this finding remains consistent following a series of robustness checks. (2) An analysis of the mechanisms indicates that the watershed compensation policy exerts its impact on the advancement of green technology innovation ecosystems through a reduction in carbon emission intensity and the enhancement of wastewater treatment efficiency. (3) The influence of the watershed compensation policy on green technology innovation ecosystems varies according to the level of public financial expenditure and labor productivity. This research offers a factual foundation for comprehending the effects of watershed compensation policies on the innovation of green technologies within China.